Global research hotspots and trends of the vaccines: Based on ESI hot papers - Meixin He; Runfeng Shi; Huilin Cao; Yuyu Wang; Yue Zhu; Xinyu Wang; Liming Liang; Xu Xia (Human Vaccines & Immunotherapeutics)
The aim of this study was to determine the characteristics of the Essential Science Indicators (ESI) hot papers on vaccine research and to provide a summary of the hot spots and development trends in the field. A systematic and comprehensive search for literature on vaccine research was conducted in the Web of Science Core Collection, and 81 ESI hot papers were obtained. A total of 81 ESI Hot Papers from 51 journals were identified in the domain of vaccines, of which 93.8% were highly cited. The United States emerged as the predominant nation in the field, contributing to 65.43% of the identified hot papers and 74.19% of the cited hot papers. The institutions with the highest number of hot papers and citations were from the United States and the United Kingdom. The analysis of collaboration networks revealed extensive research partnerships within the United States. A significant proportion of the ESI Hot Papers, amounting to 81.5%, was published in leading journals. The most prevalent keywords included infection, vaccine, and Corona Virus Disease 2019 (COVD-19). The analysis provided insights into vaccine research trends, helping clinicians and researchers quickly identify hot information in the field and facilitating vaccine application and development.